Cultivation of Sea Grape (Caulerpa racemosa) Laboratory Scale With Recirculating Air System (RAS) Methods - Erbabley, Nally Y.G.F.; Syahailatua , Diana Y.; Kelabora , Dominggas M.; Yaurwulan, Hasnawaty (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2025)
This study aims to determine the growth rate of C. racemosa reared in laboratory-scale controlled tanks using the recirculating air system (RAS) method. This research was conducted from June to August 2024 at the Mariculture Laboratory of Tual State Fisheries Polytechnic. C. racemosa sea grape seedlings were taken from the waters of Letman, Southeast Maluku with the characteristics of fresh, many grains, bright green, clean and free of other types of seaweed. Maintenance was carried out in baskets in controlled tanks. The results showed that C. racemosa cultivated using the RAS method gave varying yields among baskets in tanks with the highest weight difference in (K1) of 901 grams and the lowest in (K3) of 416 grams. The absolute growth rate of sea grapes (lat) in basket 1 and basket 4 is better than basket 2, basket 3. The percentage of daily growth rate of C. racemosa cultivated shows the highest percentage in K1 by 40% and the lowest in K3 by 12%. Based on the results obtained, the percentage of lat growth with the RAS method can be categorized as feasible, because the percentage of daily growth of seaweed is around 23% per day